Potency of tea plant indigenous microbe on plant growth and to against blister blight disease (Exobasidium vexans Massee) - Fani Fauziah; Mieke Rochimi Setiawati; Dwi Ningsih Susilowati; Eko Pranoto; Yati Rachmiati (Research Institute for Tea and Cinchona, 2016)
The chemical control method of blister blight (Exobasidium vexans Massee) on tea could inflict various negative impacts. In order to obtain an environmentally sound control method of blister blight disease, a nursery trial has been conducted to know the effectiveness of bacterial combinations. The trial was carried out at Gambung experimental garden, with seven treatments and four replications. The indigenous microbial codes are Azoto II-1, Endo-5 and Endo-76. The treatments tested comprised: control (without bacteria),Â Azoto II-1 25% + Endo-5 75%; Azoto II-1 50% + Endo-5 50%; Azoto II-1 75% + Endo-5 25%;Â Azoto II-1 25% + Endo-76 75%; Azoto II-1 50% + Endo-76 50%; and Azoto II-1 75% + Endo-76 25%. All of the treatments was applied as a soil drench, 50 ml/plant with bacterial concentration at 0,5%. The parameter observed was blister blight disease intensity, plant heights, stem diameter, leaves number, root length, and root volume. The results showed that the combination of Azoto II-1 75% + Endo-5 25% could suppress the intensity of blister blight disease with disease intensity 1.27%. The treatments also affected plant heights, stem diameter, leaves number, root length, and root volume, 15.32 cm; 3.38 cm; 8.05 cm; 18.25 cm and 2.37 cm, respectively.